Detection of wall and neck calcification of unruptured intracranial aneurysms with flat-detector computed tomography. Issue 3 (June 2016) - Kizilkilic, Osman; Huseynov, Eldeniz; Kandemirli, Sedat G; Kocer, Naci; Islak, Civan
Object: Microsurgical clipping is a widely used surgical technique in intracranial aneurysm treatment. It can be difficult in large sized aneurysms, and those with wide necks, thick walls and calcification located in the vicinity of the neck. This study reviewed calcification of the intracranial aneurysm wall and its relation to patient age, gender, location and size of the aneurysm. A possible cut-off value after which the aneurysm calcification rate increases was also investigated to classify patients' risk factors for microclipping. Methods: A retrospective review of all unruptured intracranial aneurysms that underwent digital subtraction angiography at a single centre was performed. Flat-detector computed tomography images of the aneurysm were reviewed for aneurysm location, size and calcification. The independent samples t test and χ 2 test were used to show the relation between aneurysm wall calcification and patient age, gender, aneurysm localisation and size. Results: None of the reviewed factors were statistically significantly related to aneurysm calcification except aneurysm size ( P < 0.01). Receiver operating characteristic curves showed aneurysms greater than 10.5 mm could be predicted to be calcified with a sensitivity of 80% and specificity of 63%. Conclusion: In this study, the presence of calcification was related to aneurysm size. Larger aneurysms were more likely to be calcified. Aneurysms greater than 10.5 mm should be further investigated with a modality such as flat-detector computed tomography to show the calcification in detail, especially if microclipping is considered.